Torsion of Rectangular HSS and Box Section Members: A Critical Review - Dowswell, Bo (Engineering Journal, 2026)
The purposes of this paper are to summarize the research on the torsional performance of square and rectangular hollow section members and compare the available experimental results to the applicable provisions in the AISC Specification (2022). A review of the research on the torsional strength of square and rectangular hollow section members revealed 49 experimental tests from 11 projects. A first-order reliability analysis was used to calculate appropriate resistance factors for the current design equations, revealing inconsistent reliability indices that are dependent on the predicted failure mode. Revisions are proposed for the provisions in AISC Specification Section H3.1 that result in a simpler design method with increased accuracy. Also, the accuracy of serviceability rotation calculations is evaluated using the available experimental data.